Pengaruh Self-Acceptance Terhadap Coping Strategy Orang Tua Dengan Anak Down Syndrome Di Yayasan Persatuan Orang Tua Down Syndrome (POTADS) - Pratiwi Jessy Saputri; Zirmansyah Zirmansyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Parents who have children with Down syndrome experience various dynamics and problems to be able to accept the circumstances that occur. Parents' self-acceptance is an important aspect in caring for, educating, and raising the baby. This study aims to determine the effect of self-acceptance on coping strategies of parents who have children with Down syndrome. Research using quantitative methods with a sample of 287 parents, who are members of the Down Syndrome Parents Association Foundation (POTADS). there are 46 statement items on the coping strategy scale (r = 0.873) and 16 items on the self-acceptance scale (r = 0.714) on a Likert model scale. The results of data analysis using simple linear regression tests show that there is a significant effect of self-acceptance on coping strategies with a sig value. <0.05. through the regression equation Ŷ= 77.608 + 1.090X. The correlation coefficient value is 0.489 and the coefficient of determination (R Square = 0.239). 23.9% self-acceptance influences the coping strategy of parents at the POTADS Foundation.